PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA PADA MATERI PROGRAM LINEAR - Titut Wulandari (Absis: Mathematics Education Journal, 2020)
The objective of this study is to improve mathematics learning achievement through Cooperative Learning Type Think Pair Share in Linear Program. The subject is student of class XI IIS1 of SMA Negeri 1 Magetan in the academic year 2019/2020. This research action is carried out in two cycles. The results of the pre-cycle research is obtained data on students who completed learning as many as 18 students with a percentage of 60% with a class average of 72.5. In the first cycle, the data is obtained from students who completed learning 20 students with a percentage of 65% with a class average of 76.25 in the second cycle 26 students have completed learning with a percentage of 85% with the class average 82. This result  indicates an increase in each cycle, so it can be concluded that the use of the Think Pair Share method can improve student learning achievement in class XI IIS1 SMA Negeri 1 Magetan.